Evaluasi Program Ketahanan Pangan dalam Ketersediaan Pangan pada Dinas Ketahanan Pangan Kabupaten Malinau - Freddy, Christoforus; Muhtar, Entang Adhy; Wahyudi, Heri (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Limitations and the absence of an effective working mechanism, not yet well accessed, and the assessment of PPH (Pola Pangan Harapan) has not met the minimum service standard value of 83.2 in Malinau Regency. In this research135xddg1 the theory used refers to the dimensions/characteristics of programme evaluation from William Dun through 4 (four) stages (1) Value Focus, (2) Fact-Value Interdependence, (3) Present and Past Orientation, and (4) Value Duality. The results of the analysis show that the per capita availability of Malinau Regency's Total Food Balance (NBM) for kcal/day energy availability is 2,663 and the total score of Pola Pangan Harapan (PPH) at the availability level of Malinau Regency in 2021 is 81.50, explaining that the resulting PPH score is still below the National SPM of 83.2